Relating polar bears killed, human presence, and ice conditions in Svalbard 1987–2019 - Vongraven, D.; Amstrup, S. C.; McDonald, T. L.; Mitchell, J.; Yoccoz, N. G. (Frontiers in Conservation Science, 2023)
Conflicts between humans and polar bears have been predicted to increase as polar bear prime habitat, sea ice, is decreasing. In Svalbard, a strict protection and control schemes have secured near complete records of bears killed and found dead since 1987. We analyzed the trend in the number of kills and related this to human visitation to the archipelago. We found a slight decrease in the number of kills in the period 1987-2019, and a decrease in per capita number of kills when monthly kills were compared to the monthly number of visitors disembarking in the main settlement. We then used a discrete choice resource selection model to assess whether polar bear kill events are related to attributes of the kill sites and environmental conditions at the time. We divided Svalbard in four sectors, North, East, South, and West, and monthly average ice cover was calculated in 25-km rings around Svalbard, rings that were further delineated by the four sectors. We found that the odds of a kill was greater along the shoreline, and that the odds would be reduced by 50% when moving only 900 m from the shoreline when all sectors were included. Distance from other covariates like settlements, trapper's cabins, and landing sites for tourists did for the most part not have a significant impact on the odds of a kill. Sectorwise, ice cover had no significant impact on the odds for a kill. The decreasing trend in kills of polar bears might partly be explained by the success of strict protection and management regimes of Svalbard wilderness.